Advances in xenogeneic donor decellularized organs: A review on studies with sheep and porcine-derived heart valves - Inal, Muslum Suleyman; Avci, Huseyin; Hassan, Shabir; Darcan, Cihan; Shin, Su Ryon; Akpek, Ali (WILEY, 2024)
Heart valve replacement surgeries are performed on patients suffering from abnormal heart valve function. In these operations, the problematic tissue is replaced with mechanical valves or with bioprosthetics that are being developed. The thrombotic effect of mechanical valves, reflecting the need for lifelong use of anticoagulation drugs, and the short-lived nature of biological valves make these two types of valves problematic. In addition, they cannot adapt to the somatic growth of young patients. Although decellularized scaffolds have shown some promise, a successful translation has so far evaded. Although decellularized porcine xenografts have been extensively studied in the literature, they have several disadvantages, such as a propensity for calcification in the implant model, a risk of porcine endogenous retrovirus (PERV) infection, and a high xenoantigen density. As seen in clinical data, it is clear that there are biocompatibility problems in almost all studies. However, since decellularized sheep heart valves have not been tried in the clinic, a large data pool could not be established. This review compares and contrasts decellularized porcine and sheep xenografts for heart valve tissue engineering. It reveals that decellularized sheep heart valves can be an alternative to pigs in terms of biocompatibility. In addition, it highlights the potential advantages of bioinks derived from the decellularized extracellular matrix in 3D bioprinting technology, emphasizing that they can be a new alternative for the application. We also outline the future prospects of using sheep xenografts for heart valve tissue engineering.
Keywords: decellularization; heart valve; regenerative medicine; tissue engineering; xenografts; VENTRICULAR OUTFLOW TRACT; EXTRACELLULAR-MATRIX BIOINK; GUIDED TISSUE REGENERATION; ENGINEERED PULMONARY VALVE; MESENCHYMAL STEM-CELLS; AORTIC-VALVE; IN-VITRO; CRYOPRESERVED ALLOGRAFTS; HISTOLOGICAL-EVALUATION; STRUCTURAL-PROPERTIES; Biotechnology & Applied Microbiology; Engineering; Pharmacology & Pharmacy